Thanksgiving in the perspective of spiritual and moral development - Samolej, Anna (Studia Teologiczne Białystok Drohiczyn Łomża, 2025)
The Eucharist is a unique mystery of thanksgiving that shapes human life and spirituality. Thanksgiving has the power to shape the moral dimension of human life and the sacramental community. The community, as the medium and subject of faith, is immersed in God's communication with others and thus becomes a space for a communal exchange of love. The banquet is an epiphany of God, in which He provides the nourishment that creates community, a space for freedom of encounter, exchange, connection, and unification in eschatological dimensions. This, of course, requires moral commitment, reciprocity, and a will to communion. This also implies the need for social engagement, even a mission that is sometimes critical of society.